Pogostemon parviflorus promoting apoptosis of cervical cancer cell line: An In-vitro study - Harsha Thanvi; Jayshree Changade; Vaibhav Sunil Ladke (Natural Resources for Human Health, 2026)
Cervical cancer is prevalent among women and is associated with a significant mortality rate. Chemotherapy is frequently employed as a treatment modality; however, its efficacy in addressing cervical cancer is constrained by significant side effects and the development of treatment resistance. The research evaluates the anticancer properties of Pogostemon parviflorus extract on a human cervical cancer cell line. The hydroalcoholic extract of the leaf portion of P. parviflorus was meticulously prepared employing established methodologies. The research investigated the anticancer properties of the plant using various in vitro methodologies, including 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide assays, apoptosis evaluation, cell cycle analysis, assessment of reactive oxygen species, mitochondrial membrane potential analysis, and RT-PCR for gene expression profiling. The findings indicated a pronounced cytotoxic effect, characterized by early apoptosis and disturbances in the sub-G0 phase of the cell cycle. The presence of P. parviflorus resulted in a significant reduction of reactive oxygen species within cells. The analysis of gene expression revealed significant effects on the BAX, BCL-2, and cMYC genes, indicating the onset of early apoptosis and demonstrating antiproliferative effects. This study reveals that P. parviflorus may serve as a promising candidate for the treatment of cervical cancer, owing to its cytotoxic, antiproliferative, apoptotic, and antioxidant characteristics. Additional investigation is necessary to elucidate its mechanism and substantiate its viability as a prospective cancer therapy.